Perception of infrastructural development and tax compliance among small and medium scale enterprises in Lagos state: The mediating role of taxpayers’ satisfaction with revenue utilization - Oyewumi, Obafemi Rufus (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
Purpose: This study investigates how small and medium-sized enterprises (SMEs) in Lagos State, Nigeria, perceive infrastructural development and how these perceptions influence their tax compliance behaviour, using taxpayers’ satisfaction as a mediating variable.Methodology: The study used both secondary and primary sources to collect relevant data. The study adopted a survey research design. A total of 42,072 small and medium enterprise owners in Lagos State were the population, out of which a sample size of 400 was drawn. Four hundred (400) copies of the questionnaire were administered, and 364 were returned, while only 342 copies were usable. The data collected were analyzed using descriptive and inferential statistics. Three hypotheses were formulated and tested using regression analysis; Process Macro on SPSS was used to test the fourth hypothesis, testing the mediating effects of taxpayers’ satisfaction on the relationship between infrastructure development and tax compliance.Results and conclusion: Results show that infrastructural development significantly impacts taxpayers’ satisfaction with government spending and compliance with tax regulations. The study further revealed that taxpayers’ satisfaction plays a mediating role in the relationship between infrastructural development and tax compliance. Based on this finding, it is recommended that the Lagos State government should continue to enhance the provision and quality of infrastructure to improve taxpayers’ satisfaction and, in turn, foster greater compliance among residents.Implication of findings: The findings imply that the level of infrastructural development influences the satisfaction derivable by SME from government spending, and by extension, the relationship between infrastructural development and tax compliance.
Keywords: Revenue utilisation; Infrastructure development; Tax compliance; Fiscal exchange; Satisfaction